Is Caring a Health Hazard? The Mental Health and Vitality of Carers of a Person with a Disability in Australia - Higgins, Daryl J; Edwards, Benjamin (My University, 2009)
Objective: To compare the mental health and vitality of people caring for a family member with a disability with those of the general population. Second, to identify factors experienced by carers that put them at risk of poor mental health and vitality. Design: Cross-sectional design where logistic and multiple regression analyses were used to compare rates of mental health problems and vitality between carers and the general population while controlling for demographic characteristics. In addition, logistic and multiple regression using data from the survey of carers were used to identify risk factors for poor mental health and vitality that were particular to caregiving. Participants and setting: A randomly selected representative survey of 1002 carers from the Australian Centrelink administrative database (June 2006) who received government payments to care for a person with a disability or severe medical condition, or a person who was frail aged. A sample of 10 223 non-carers was drawn from the fourth wave of the Household, Income and Labour Dynamics in Australia Survey, a nationally representative household panel survey (August 2004 to February 2005). Main outcome measures: Mental health and vitality as measured by the Medical Outcomes Study 36-item Short-Form Health Survey. Results: Compared with the general population, carers were at significantly greater risk of having a mental health problem and lower levels of vitality, even after controlling for demographic characteristics. For carers, the risk factors for poor mental health and lower levels of vitality were caring for a person with a disability with higher care needs, experiencing greater levels of financial stress, lower levels of support and worse family functioning. Conclusion: Carers are at greater risk of mental health problems and lower energy levels than the general population.
The Medical Journal of Australia
Keywords: Health -- Mental; Carers -- of Disabled; Health; Carers; Health and wellbeing; Health; Carers; of Disabled; Mental; Health and wellbeing